Assessment of Smartphone Addiction And It’s Consequence Among Undergraduate Students in Four Colleges In Gadag City, Karnataka - Ms. Manjula Patil (Journal of Medical Biomedical and Applied Sciences, 2023)
Background: A smartphone is a hybrid of a cell phone and a handheld computer that has transformed in the greatest technological revolution in Internet history. Nomophobia, or the fear of being without your phone, is the official term for smartphone addiction. The Smartphone has become an indispensable part of everyday life. The problem of smartphone addiction is spreading throughout the world, particularly among students. Objectives: To determine the prevalence of smartphone addiction among undergraduate students. To identify the risk factors associated with mobile usage among undergraduate students. To assess the effects of smartphone addiction among undergraduate students. Materials and Methods: A cross-sectional organizational study was conducted among college students in Gadag city, Karnataka. A semi-structured pre-tested questionnaire was used to collect quantitative data. The sample size was 400, which was calculated using the Prevalence formula. The study participants were chosen using a systematic sampling method. The data was entered into a sheet, and the results were expressed as a frequency and percentage. Results: There were 46.5 percent males and 53.5 percent females among the 400 students. The study participants’ average age was 20.5 2 years. Every single student has a smartphone. 34.8 percent of students use their smartphone 4-6 hours per day, with social networking being the primary reason. According to the study findings, 29.3 percent of students were addicted to their smartphones. Male students were more addicted to smartphones than female students. Conclusion: Smart phone addiction is prevalent and must be addressed seriously. This can be addressed through better lifestyle changes, increased awareness, and behavioral changes.